E-HRM practices and sustainable competitive advantage from HR practitioner’s perspective: A mediated moderation analysi - Mohamed Dawood Shamout (Growing Science, 2022)
This paper seeks to investigate the impact of Electronic Human Resource Management (e-HRM) practices on attaining Sustainable Competitive Advantage (SCA) in the context of the Jordanian Industrial Sector (JIS) and identify the mediating role of e-HRM Perceived Usefulness (PU) and e-HRM Perceived Ease of Use (PEOU). Furthermore, it investigates the moderating role of User Satisfaction and e-HRM Continuance Usage Intention. To achieve the paper objectives, a Mediated-Moderation Model was designed. The researchers distributed (750) questionnaires, (615) questionnaires were returned and validated for analysis in HRM and development divisions and based on a Census method with the response rate was about (82%). The ‘Structural Equation Modeling’ (SEM) methodology was used, and for analysis, SPSS and Amos were applied. The results indicated that e-HRM practices had significant influence on SCA. The paper also demonstrated that there was a significant mediate effect of TAM constructs on the relationship between e-HRM practices and SCA. Finally, the findings indicated that the user satisfaction and e-HRM continuance usage intention did not moderate the relationship between e-HRM-PEOU and PU and SCA path.